Insulation coated magnetic powder and preparation method and application thereof

By forming a porous carbon layer on the surface of the magnetic powder, adsorbing metal ions, and then performing oxygen partial pressure heat treatment, the problem of uneven and dense insulation coating in the prior art is solved, and a magnetic powder core with high resistivity, high DC superposition characteristics and low power loss is achieved.

CN119560290APending Publication Date: 2025-03-04HENGDIAN GRP DMEGC MAGNETICS CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411700019.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The prior art is difficult to achieve uniform and dense insulating coating on the surface of magnetic powder, resulting in low resistivity, high power consumption and poor DC superposition characteristics of the magnetic powder core.

Method used

The magnetic powder is mixed with a carbon source in a solvent, and a porous carbon layer is formed by hydrothermal reaction, and then reacted with a metal salt to absorb metal ions. Finally, the porous carbon layer is heat-treated under oxygen partial pressure to form a dense, uniform and complete insulating oxide layer.

Benefits of technology

The insulation coating density and integrity of the magnetic powder surface are improved, the resistivity and DC superposition characteristics of the magnetic powder core are enhanced, and power loss is reduced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to insulation coated magnetic powder and a preparation method and application thereof, the preparation method comprises the following steps: (1) mixing magnetic powder, a carbon source and a first solvent, and carrying out a hydrothermal reaction to obtain first magnetic powder, the first magnetic powder comprising the magnetic powder and a porous carbon layer located on the surface of the magnetic powder; (2) the first magnetic powder, metal salt and a second solvent are mixed to obtain second magnetic powder, and the second magnetic powder comprises the magnetic powder, a porous carbon layer located on the surface of the magnetic powder and metal ions adsorbed on the surface of the porous carbon layer; and (3) carrying out heat treatment on the second magnetic powder in an oxygen-containing atmosphere to obtain the insulation coated magnetic powder. The surface of the insulated coated magnetic powder provided by the invention is coated with the insulated oxide layer which is high in compactness, good in uniformity and integrity and high in bonding strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnetic materials, and in particular to an insulating coated magnetic powder and a preparation method and application thereof. Background Art

[0002] As a soft magnetic material with high saturation magnetic induction intensity, good frequency characteristics and good temperature stability, magnetic powder cores are widely used in devices such as power factor correctors (PFC inductors), pulse flyback transformers and energy storage filter inductors. As for metal magnetic powder cores, improving resistivity and reducing power consumption have always been difficult problems that researchers need to solve.

[0003] The existing preparation methods for improving the resistivity of metal magnetic powder cores generally involve mixing high-resistivity oxides such as kaolin, silica, mica powder, and alumina with magnetic powder, or using aluminum dihydrogen phosphate and strong acids such as phosphoric acid and nitric acid to react with magnetic powder to generate high-resistivity iron oxides. Although this method is simple to operate, the bonding strength between the oxide and the magnetic powder is poor, it is easy to fall off during molding, and the uniformity and integrity of the coating are poor. The resistivity of the obtained magnetic powder core is relatively low, the power consumption is high, and the DC superposition characteristics are poor. Therefore, how to further improve the resistivity of metal magnetic powder cores and thus improve product performance has become a major challenge in current research.

[0004] In addition, with the rapid development of science and technology, the miniaturization and lightweight of equipment have led to the development of electronic devices towards miniaturization and high power density. Therefore, the magnetic powder core materials in electronic devices need to have high magnetic flux density, high DC bias performance, and high frequency and low loss characteristics to adapt to the development of electronic devices.

[0005] In the process of preparing magnetic powder cores with excellent performance, powder insulation coating is one of the most critical links. Powder insulation coating refers to coating the surface of magnetic powder particles with a layer of insulating material with high resistivity by physical or chemical methods, thereby reducing the eddy current loss of the product and improving the DC superposition characteristics. At present, the most common powder coating method is to add oxide insulating agents to the powder or use acid passivating agents to react chemically with the magnetic powder to generate iron oxide with high resistivity, and finally add glue to improve the formability of the powder. The powder prepared by this method has poor uniformity, density and integrity of the insulation coating layer, and the DC superposition and power loss of the pressed sample ring are poor.

[0006] Prior art CN103247403A discloses a method for preparing a metal soft magnetic powder core, which directly uses nano oxide dispersion and sodium silicate powder to insulate and coat metal magnetic powder, wherein 6.7wt% nano MgO dispersion and 0.8% sodium silicate powder are used when coating Sendust magnetic powder, and finally a Sendust magnetic core is prepared. The nano oxide dispersion has a good dispersion effect, but the nano particles have poor adhesion to the magnetic powder, making it difficult to achieve uniform coating, and are easy to fall off during the pressing process, resulting in poor insulation performance of the metal soft magnetic powder core, high loss, and low DC superposition characteristics.

[0007] Prior art CN101089108A ​​discloses an inorganic insulating binder for metal soft magnetic powder core and its preparation method, wherein the inorganic insulating binder is a mixture of SiO2, Al2O3, ZrO2, mica powder and water, and the suspended particles in the hydrate solution are close to the nanometer scale, which has the dual effects of insulation and bonding. The bonding effect can be enhanced during the heat treatment process to improve the stability of the powder core. Although the performance of the inorganic insulating binder is stable, the coating effect is not ideal, and it is difficult to achieve uniform and dense coating on the surface of the magnetic powder, which deteriorates the performance of the magnetic powder core.

[0008] Prior art CN116435083A discloses a double inorganic coated magnetic powder core and a preparation method thereof, wherein the surface of the magnetic powder is first treated with a surfactant and a surface conditioning agent, then the magnetic powder is passivated with an aqueous solution of nitrate and dihydrogen phosphate, and finally a resin and a coupling agent are used for bonding and granulation. The double inorganic coating layer of the invention can improve the insulation effect and antioxidant capacity of the magnetic powder, but the thermal stability, coating uniformity and integrity of the nitrate and dihydrogen phosphate insulating agents used are poor, which leads to a decrease in the insulation of the material, poor high-frequency magnetic properties, and large eddy current losses, thereby affecting the stability of the performance of the magnetic powder core.

[0009] Therefore, providing a preparation method that can improve the density, uniformity and integrity of the magnetic powder insulation coating, thereby improving the resistivity and DC superposition characteristics of the magnetic powder core, and reducing the magnetic loss of the magnetic powder core has become an urgent problem to be solved. Summary of the invention

[0010] In order to solve the above technical problems, the purpose of the present invention is to provide an insulating coated magnetic powder and a preparation method and application thereof. The present invention first mixes the magnetic powder with a carbon source in a solvent, and then forms a porous carbon layer on the surface of the magnetic powder through a hydrothermal reaction, and then reacts with a metal salt in a solvent. The porous carbon layer on the surface of the magnetic powder adsorbs metal ions in the metal salt. Then, a heat treatment process under oxygen partial pressure forms an insulating oxide layer with high density, good uniformity and integrity, and high bonding strength on the surface of the magnetic powder. The prepared insulating coated magnetic powder forms a magnetic powder core with the advantages of high resistivity, high DC superposition characteristics and low power loss.

[0011] To achieve this object, the present invention adopts the following technical solutions:

[0012] In a first aspect, the present invention provides a method for preparing an insulating coated magnetic powder, the preparation method comprising the following steps:

[0013] (1) mixing a magnetic powder, a carbon source and a first solvent, and subjecting the mixture to a hydrothermal reaction to obtain a first magnetic powder, wherein the first magnetic powder includes the magnetic powder and a porous carbon layer on a surface of the magnetic powder;

[0014] (2) mixing the first magnetic powder, the metal salt and the second solvent to obtain a second magnetic powder, wherein the second magnetic powder includes the magnetic powder, a porous carbon layer located on the surface of the magnetic powder, and metal ions adsorbed on the surface of the porous carbon layer;

[0015] (3) Heat treating the second magnetic powder in an oxygen-containing atmosphere to obtain the insulating coated magnetic powder.

[0016] The present invention mixes magnetic powder and a carbon source in a solvent, generates a porous carbon layer on the surface of the magnetic powder through a hydrothermal reaction, and then mixes the first magnetic powder containing the porous carbon layer with a metal salt in a solvent, utilizes the adsorption effect of hydroxyl and carboxyl groups on the surface of the porous carbon layer on metal ions, so that the porous carbon layer on the surface of the magnetic powder is rich in metal ions, and then places the obtained second magnetic powder in an oxygen-containing atmosphere for a heat treatment process to control the decomposition of the porous carbon layer and the formation of metal oxides, thereby obtaining a magnetic powder with a high density of surface-coated metal oxides, good coating uniformity and integrity, and high bonding strength, which can promote the magnetic powder core composed of the insulating coated magnetic powder to have the advantages of high resistivity, high DC superposition characteristics and low power loss.

[0017] Preferably, the magnetic powder in step (1) comprises any one of iron silicon magnetic powder, sendust magnetic powder or iron nickel magnetic powder.

[0018] Optionally, the iron silicon magnetic powder is composed of 3.5-6.5wt% Si and the balance Fe.

[0019] Optionally, the Sendust magnetic powder comprises 4.0-7.0wt% Al, 7.5-10wt% Si and the balance Fe.

[0020] Optionally, the iron-nickel magnetic powder comprises 43-50 wt % Ni and the remainder Fe.

[0021] Preferably, the particle size of the magnetic powder in step (1) is less than 150 mesh, for example, 150 mesh, 160 mesh, 170 mesh, 180 mesh, 190 mesh or 200 mesh.

[0022] Optionally, the present invention prepares magnetic powder with a particle size of less than 150 meshes by a gas atomization method.

[0023] Preferably, in step (1), the magnetic powder is first pretreated and then the mixing is performed.

[0024] Preferably, the pretreatment includes annealing pretreatment.

[0025] The present invention performs annealing pretreatment on the existing magnetic powder, which has the function of reducing the stress generated by the powder during the preparation process and transportation process, thereby reducing the power consumption of the material.

[0026] Preferably, the pretreatment further comprises performing surface pretreatment on the magnetic powder after annealing pretreatment.

[0027] Preferably, the temperature of the annealing pretreatment is 600-900°C, for example, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C or 900°C.

[0028] Preferably, the heating rate of the annealing pretreatment is 3-10°C / min, for example, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min.

[0029] Preferably, the annealing pretreatment time is 0.5-2 h, such as 0.5 h, 1 h, 1.5 h or 2 h.

[0030] Preferably, the atmosphere of the annealing pretreatment includes any one of a hydrogen atmosphere, a nitrogen atmosphere or an argon atmosphere, or a combination of at least two of them.

[0031] Preferably, the specific process of the surface pretreatment includes: mixing a surface treatment agent with the annealed pretreated magnetic powder, and then drying to obtain the pretreated magnetic powder for mixing with the carbon source.

[0032] The present invention uses a surfactant to perform surface treatment on the magnetic powder to increase the surface tension of the magnetic powder, thereby making the layer structure obtained by the treated powder in the porous carbon layer formation stage more uniform and complete, thereby promoting the coating density, uniformity and completeness of the obtained insulating coated magnetic powder to be better.

[0033] Preferably, the surface treatment agent includes any one of polyvinyl alcohol, polyoxyethylene ether or alkylphenol polyoxyethylene ether.

[0034] Preferably, the concentration of the surface treatment agent is 15-23wt%, such as 15wt%, 17wt%, 19wt%, 21wt% or 23wt%.

[0035] Preferably, during the surface pretreatment process, the mass ratio of the surface treatment agent to the magnetic powder is (0.04-0.07):1, for example, 0.04:1, 0.045:1, 0.05:1, 0.055:1, 0.06:1, 0.065:1 or 0.07:1, etc.

[0036] Preferably, during the surface pretreatment process, the drying temperature is 60-150°C, for example, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C, etc.

[0037] Preferably, during the surface pretreatment process, the drying time is 30-120 min, for example, 30 min, 50 min, 70 min, 90 min, 110 min or 120 min.

[0038] Preferably, the carbon source in step (1) comprises a carbon source containing hydroxyl groups and / or carboxyl groups.

[0039] Preferably, the carbon source in step (1) comprises any one of glucose, fructose, sucrose, maltose, starch and citric acid, or a combination of at least two thereof.

[0040] Preferably, in step (1), the first solvent comprises water.

[0041] Preferably, the specific process of the mixing in step (1) includes: mixing the carbon source with the first solvent to obtain a carbon source solution, and then mixing the carbon source solution with the magnetic powder to obtain a mixed solution for hydrothermal reaction.

[0042] Preferably, the concentration of the carbon source in the carbon source solution is 7-20wt%, for example, 7wt%, 9wt%, 11wt%, 13wt%, 15wt%, 17wt%, 19wt% or 20wt%.

[0043] In the present invention, the carbon source concentration will affect the coating effect of the prepared insulating coated magnetic powder. If the carbon source concentration is too low, a well-coated porous carbon layer cannot be formed on the surface of the magnetic powder, and the porous carbon layer cannot effectively adsorb metal ions, so that the insulating coating density and integrity of the finally prepared magnetic powder are poor, affecting the resistivity, DC superposition characteristics and loss characteristics of the magnetic powder core formed by the insulating coated magnetic powder; if the carbon source concentration is too high, the carbon layer formed on the surface of the magnetic powder will be too thick, and in the subsequent heat treatment process of oxygen partial pressure, the porous carbon layer in the intermediate product cannot be completely removed, thereby affecting the resistivity, inductance characteristics and DC superposition characteristics of the magnetic powder core obtained later.

[0044] Preferably, the mass ratio of the magnetic powder to the carbon source solution is (2-4):1, such as 2:1, 2.5:1, 3:1, 3.5:1 or 4:1.

[0045] Preferably, the temperature of the hydrothermal reaction in step (1) is 225-260°C, for example, 225°C, 230°C, 235°C, 240°C, 245°C, 250°C, 255°C or 260°C.

[0046] In the present invention, the temperature of the hydrothermal reaction will affect the performance of the obtained insulating coated magnetic powder. If the temperature of the hydrothermal reaction is too low, a porous carbon layer with good coating properties cannot be formed on the magnetic powder, affecting the subsequent adsorption of metal ions; if the temperature of the hydrothermal reaction is too high, the carbon layer coating thickness will be too thick, and the porous carbon layer cannot be completely decomposed during the subsequent heat treatment process, affecting the performance of the insulating coated magnetic powder and the performance of the magnetic powder core composed of it.

[0047] Preferably, the hydrothermal reaction time in step (1) is 30-90 min, for example, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min or 90 min.

[0048] Preferably, after the hydrothermal reaction in step (1), the product of the hydrothermal reaction is subjected to a first separation, a first washing, a first drying and a magnetic separation in sequence.

[0049] Preferably, the first drying temperature is 70-100°C, such as 70°C, 80°C, 90°C or 100°C.

[0050] Preferably, the first drying time is 1-2 hours, such as 1 hour, 1.5 hours or 2 hours.

[0051] Optionally, after the magnetic separation, the magnetically separated product is further subjected to a first crushing treatment.

[0052] Preferably, the metal salt in step (2) comprises any one of iron salt, aluminum salt, titanium salt, zinc salt, magnesium salt, nickel salt or manganese salt, or a combination of at least two thereof.

[0053] Preferably, the iron salt includes any one of ferric chloride, ferric sulfate or ferric nitrate, or a combination of at least two of them.

[0054] Preferably, the aluminum salt includes any one of aluminum chloride, aluminum sulfate or alum, or a combination of at least two of them.

[0055] Preferably, the titanium salt comprises titanium chloride and / or tetrabutyl titanate.

[0056] Preferably, the zinc salt comprises zinc carbonate and / or zinc sulfate.

[0057] Preferably, the magnesium salt includes any one of magnesium chloride, magnesium sulfate or magnesium citrate, or a combination of at least two thereof.

[0058] Preferably, the nickel salt comprises nickel chloride and / or nickel sulfate.

[0059] Preferably, the manganese salt comprises manganese carbonate and / or manganese dihydrogen phosphate.

[0060] Preferably, in step (2), the second solvent comprises any one of water, ethanol, acetone or toluene, or a combination of at least two thereof.

[0061] Preferably, the specific process of the mixing in step (2) includes: mixing a metal salt with a solvent to obtain a metal salt solution, and then mixing the obtained metal salt solution with the first magnetic powder to obtain a second magnetic powder.

[0062] Preferably, the concentration of the metal salt solution is 6-12wt%, for example 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt% or 12wt%.

[0063] The present invention selects a metal salt solution of a specific concentration, which can regulate the adsorption content of metal ions on the surface of the porous carbon layer in the first magnetic powder, thereby optimizing the performance of the insulating coated magnetic powder and the resistivity and DC superposition characteristics of the magnetic powder core constituted by it, and effectively reducing the magnetic loss of the magnetic powder core.

[0064] Preferably, the ratio of the amount of the metal salt solution added to the amount of the magnetic powder added in step (1) is 1:(2-4), for example, 1:2, 1:2.5, 1:3, 1:3.5 or 1:4, etc.

[0065] Preferably, the mixing in step (2) is accompanied by heating.

[0066] Preferably, the mixing temperature in step (2) is 25-50°C, such as 25°C, 30°C, 35°C, 40°C, 45°C or 50°C.

[0067] Preferably, the mixing time in step (2) is 1-6 h, for example, 1 h, 2 h, 3 h, 4 h, 5 h or 6 h.

[0068] The present invention can control the adsorption content of metal ions on the surface of the carbon layer of the first magnetic powder by regulating the mixing time of the second magnetic powder and the metal salt solution, thereby optimizing the insulating coating effect on the magnetic powder.

[0069] Preferably, after the mixing in step (2), the mixed product is subjected to a second separation, a second washing and a second drying in sequence.

[0070] Preferably, the second drying temperature is 70-100°C, such as 70°C, 80°C, 90°C or 100°C.

[0071] Preferably, the second drying time is 1-2 hours, such as 1 hour, 1.5 hours or 2 hours.

[0072] Preferably, after the second drying, the product after the second drying is further subjected to a second crushing treatment.

[0073] Preferably, the temperature of the heat treatment in step (3) is 350-500°C, for example, 350°C, 370°C, 390°C, 410°C, 430°C, 450°C, 470°C, 490°C or 500°C.

[0074] The present invention adopts a specific heat treatment temperature to ensure the full decomposition of the porous carbon layer in the second magnetic powder, while regulating the grain growth of the oxide formed by the metal ions in the oxygen-containing atmosphere, thereby improving the density and integrity of the insulating coating of the magnetic powder. In addition, the temperature regulation can also avoid oxidation of the magnetic powder due to excessively high temperature, which affects the inductance characteristics and DC superposition characteristics of the subsequently prepared magnetic powder core.

[0075] Preferably, the heating rate of the heat treatment in step (3) is 2-10°C / min, for example, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, etc.

[0076] Preferably, the heat treatment time in step (3) is 0.5-2 h, such as 0.5 h, 1 h, 1.5 h or 2 h.

[0077] Preferably, the oxygen-containing atmosphere in step (3) comprises oxygen.

[0078] Preferably, the oxygen-containing atmosphere in step (3) also includes nitrogen and / or an inert gas.

[0079] Preferably, the oxygen content in the oxygen-containing atmosphere in step (3) is 5-15 vol%, for example, 5 vol%, 7 vol%, 9 vol%, 11 vol%, 13 vol% or 15 vol%.

[0080] The present invention provides an oxygen content in an oxygen-containing atmosphere, which can improve the integrity of a formed oxide film coating layer. The oxygen content can regulate the grain growth of the oxide, improve the compactness of the oxide coated on the surface of the magnetic powder, and prevent the magnetic powder from being oxidized, thereby ensuring that the obtained magnetic powder core composed of the insulating coated magnetic powder has high DC superposition, high resistivity and low magnetic loss.

[0081] As a preferred technical solution of the present invention, the preparation method comprises the following steps:

[0082] S1. annealing the magnetic powder with a particle size of less than 150 mesh at 600-900°C for 0.5-2h, wherein the heating rate of the annealing pretreatment is 3-10°C / min, and the atmosphere of the annealing pretreatment includes any one of a hydrogen atmosphere, a nitrogen atmosphere or an argon atmosphere or a combination of at least two thereof, and then mixing the annealed magnetic powder with a surface treatment agent having a concentration of 15-23wt% in a mass ratio of 1:(0.04-0.07), and then drying the annealed magnetic powder at 60-150°C for 30-120min, and sieving the annealed magnetic powder with a mesh of 60-100 mesh to obtain the pretreated magnetic powder;

[0083] S2. mixing a carbon source with a first solvent to obtain a carbon source solution with a concentration of 7-20wt%, mixing the pretreated magnetic powder with the carbon source solution in a mass ratio of (2-4):1, performing a hydrothermal reaction at 225-260°C for 30-90min, then, after separation and washing, drying at 70-100°C for 1-2h, removing the carbon source not attached to the surface of the magnetic powder by magnetic separation, and then crushing to obtain a first magnetic powder, wherein the first magnetic powder includes the magnetic powder and a porous carbon layer located on the surface of the magnetic powder;

[0084] S3. Mixing the metal salt with the second solvent to obtain a metal salt solution with a concentration of 6-12wt%, mixing the first magnetic powder with the metal salt solution under heating conditions of 25-50°C for 1-6h, wherein the ratio of the amount of the metal salt solution added to the amount of the pretreated magnetic powder added in step S2 is 1:(2-4), and after separation, washing, and then drying at 70-100°C for 1-2h, and then grinding the dried product to obtain a second magnetic powder, wherein the second magnetic powder includes the magnetic powder, a porous carbon layer on the surface of the magnetic powder, and metal ions adsorbed on the surface of the porous carbon layer;

[0085] S4. In a nitrogen and / or inert gas atmosphere containing an oxygen content of 5-15 vol%, the second magnetic powder is subjected to heat treatment at 350-500°C for 0.5-2 h, with a heating rate of 2-10°C / min, to obtain the insulating coated magnetic powder.

[0086] In a second aspect, the present invention provides an insulation-coated magnetic powder, wherein the insulation-coated magnetic powder is prepared by the preparation method described in the first aspect.

[0087] The insulating coated magnetic powder provided by the present invention has high coating density, good uniformity and integrity, and high bonding strength between the coating layer and the magnetic powder, thereby being able to improve the performance effect of the subsequently obtained magnetic powder core.

[0088] Preferably, the insulation-coated magnetic powder comprises magnetic powder and a metal oxide coated on the surface of the magnetic powder.

[0089] In a third aspect, the present invention provides a magnetic powder core, wherein the magnetic powder core comprises the insulation-coated magnetic powder described in the second aspect.

[0090] The magnetic powder core provided by the present invention includes specific insulating coated magnetic powder. The insulating oxide layer coated on the surface of the magnetic powder has high density, good uniformity and integrity, and high bonding strength, which can promote the magnetic powder core composed of the insulating coated magnetic powder to have the characteristic advantages of high resistivity, high DC superposition characteristics and low power loss.

[0091] In a fourth aspect, the present invention provides a method for preparing the magnetic powder core according to the third aspect, the preparation method comprising:

[0092] The insulating coated magnetic powder, binder and release agent described in the second aspect are mixed, and then pressed and sintered to obtain the magnetic powder core.

[0093] The preparation method of the magnetic powder core provided in the present invention adopts a specific insulating coated magnetic powder as a raw material, and combines the magnetic powder with a binder and a release agent through a compression molding combined with a sintering process, so that the magnetic powder material in the prepared magnetic powder core still has a good insulating coating effect, so that the prepared magnetic powder core has the characteristic advantages of high resistivity, high DC superposition characteristics and low power loss.

[0094] Preferably, the adhesive includes any one of silicone resin, epoxy resin, phenolic resin or acrylic resin, or a combination of at least two of them.

[0095] Preferably, the added amount of the binder is 0.3-2wt% of the mass of the insulating coated magnetic powder, for example 0.3wt%, 0.5wt%, 0.7wt%, 0.9wt%, 1.1wt%, 1.3wt%, 1.5wt%, 1.7wt%, 1.9wt% or 2.0wt%, etc.

[0096] Preferably, the release agent includes any one of zinc stearate, aluminum stearate or talc, or a combination of at least two of them.

[0097] Preferably, the release agent is added in an amount of 0.1-0.6 wt% of the mass of the insulating coated magnetic powder, such as 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt% or 0.6 wt%.

[0098] Preferably, after the mixing, the mixed product is screened.

[0099] Preferably, the mesh size of the sieve is 60-100 mesh, such as 60 mesh, 70 mesh, 80 mesh, 80 mesh, 90 mesh or 100 mesh.

[0100] Preferably, the pressure of the press molding is 1200-2200 MPa, for example, 1200 MPa, 1400 MPa, 1600 MPa, 1800 MPa, 2000 MPa or 2200 MPa.

[0101] Preferably, the sintering temperature is 600-800°C, for example, 600°C, 620°C, 640°C, 660°C, 680°C, 700°C, 720°C, 740°C, 760°C, 780°C or 800°C.

[0102] Preferably, the heating rate of the sintering is 5-15°C / min, for example, 5°C / min, 7°C / min, 9°C / min, 11°C / min, 13°C / min or 15°C / min.

[0103] Preferably, the sintering time is 0.5-2 h, such as 0.5 h, 1 h, 1.5 h or 2 h.

[0104] Preferably, the sintering temperature reduction rate is 5-10°C / min, such as 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min.

[0105] Preferably, the gas used in the sintering atmosphere includes any one of hydrogen, nitrogen or argon, or a combination of at least two of them.

[0106] Compared with the prior art, the present invention has at least the following beneficial effects:

[0107] (1) The present invention mixes a magnetic powder with a carbon source in a solvent, generates a porous carbon layer on the surface of the magnetic powder through a hydrothermal reaction, and then mixes the first magnetic powder containing the porous carbon layer with a metal salt in a solvent, and utilizes the adsorption effect of hydroxyl and carboxyl groups on the surface of the porous carbon layer on metal ions to make the porous carbon layer on the surface of the magnetic powder rich in metal ions. The obtained second magnetic powder is then placed in an oxygen-containing atmosphere for a heat treatment process to control the decomposition of the porous carbon layer and the formation of metal oxides, thereby obtaining a magnetic powder with a high density of surface-coated metal oxides, good coating uniformity and integrity, and high bonding strength, which can promote the magnetic powder core composed of the insulating coated magnetic powder to have the advantages of high resistivity, high DC superposition characteristics and low power loss.

[0108] (2) The insulating coated magnetic powder provided by the present invention has high coating density, good uniformity and integrity, and high bonding strength between the coating layer and the magnetic powder, thereby improving the performance of the subsequently obtained magnetic powder core.

[0109] (3) The magnetic powder core provided by the present invention includes a specific insulating coated magnetic powder. The insulating oxide layer coated on the surface of the magnetic powder has a high density, good uniformity and integrity, and high bonding strength. This can promote the magnetic powder core composed of the insulating coated magnetic powder to have the advantages of high resistivity, high DC superposition characteristics and low power loss.

[0110] (4) The preparation method of the magnetic powder core provided in the present invention adopts a specific insulating coated magnetic powder as a raw material, and combines it with a binder and a release agent through a compression molding combined with a sintering process, so that the magnetic powder material in the magnetic powder core still has a good insulating coating effect, so that the prepared magnetic powder core has the advantages of high resistivity, high DC superposition characteristics and low power loss. DETAILED DESCRIPTION

[0111] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0112] The Sendust magnetic powder, Iron Silicon powder and Iron Nickel magnetic powder used in the following examples are all magnetic powders of specific particle sizes prepared by a gas atomization method.

[0113] In the preparation process of the magnetic powder core involved in the following embodiments, the sample ring obtained by the pressing molding process has an inner diameter of 14.7 mm, an outer diameter of 26.9 mm, and a height of 11.2 mm.

[0114] Example 1

[0115] This embodiment provides a method for preparing insulating coated Sendust magnetic powder, the preparation method comprising the following steps:

[0116] S1. Annealing pretreatment of the sendust magnetic powder with a particle size of 150 mesh at a temperature of 810° C. for 1 hour in a nitrogen atmosphere, the heating rate of the annealing pretreatment is 5° C. / min, the Al content in the sendust magnetic powder is 5.4wt%, the Si content is 9.6wt%, and the balance is Fe. Then, 1 kg of the annealed sendust magnetic powder is mixed with a polyvinyl alcohol solution with a concentration of 20wt%, the polyvinyl alcohol solution is prepared by 10g of polyvinyl alcohol powder and 40g of water, and then dried at 120° C. for 120min, and the dried product is sieved with a sieve with a mesh number of 80 to obtain the pretreated sendust magnetic powder.

[0117] S2. Mix 20 g of sucrose with 180 g of water to obtain a sucrose aqueous solution with a concentration of 10 wt%, take 500 g of the pretreated Sendust magnetic powder obtained in step S1 and the obtained sucrose aqueous solution to perform a hydrothermal reaction at 250°C for 60 min, and after cooling, separate the products of the hydrothermal reaction, wash the separated solid with ethanol, and then dry it at 80°C for 1.5 h, use magnetic separation to remove carbon balls not attached to the surface of the magnetic powder, and then crush the magnetically separated product to obtain a first magnetic powder, wherein the first magnetic powder includes Sendust magnetic powder and a porous carbon layer on the surface of the Sendust magnetic powder.

[0118] S3. Mix 20 g of aluminum chloride and 180 g of water to obtain an aluminum chloride solution with a concentration of 10 wt%, add the first magnetic powder obtained in step S2, and mix them under heating conditions at 40°C for 2 hours. After separating the mixed product, the obtained solid is washed with ethanol, and then dried at 80°C for 2 hours, and then the dried product is crushed to obtain a second magnetic powder, wherein the second magnetic powder includes sendust magnetic powder, a porous carbon layer located on the surface of the sendust magnetic powder, and aluminum ions adsorbed on the surface of the porous carbon layer.

[0119] S4. In an oxygen-containing nitrogen atmosphere with an oxygen content of 10 vol%, the second magnetic powder obtained in step S3 is placed in a tube furnace, heated to 400°C at a heating rate of 5°C / min and heat treated for 1 hour to obtain an insulating coated Sendust magnetic powder.

[0120] This embodiment also provides a method for preparing a magnetic powder core, the preparation method comprising the following steps:

[0121] The insulating coated Sendust magnetic powder prepared above was mixed with methyl silicone resin and zinc stearate release agent, wherein the amount of methyl silicone resin added was 1wt% of the mass of the insulating coated Sendust magnetic powder, and the amount of zinc stearate added was 0.3wt% of the mass of the insulating coated Sendust magnetic powder. After drying, the mixture was sieved with a sieve with a mesh number of 80 to obtain a mixed material, and the mixed material was pressed into shape under a press at 2000MPa to obtain a sample ring. The obtained sample ring was placed in a nitrogen atmosphere, heated to 700°C at a rate of 10°C / min, and kept warm for 1h, and then cooled to 25°C at a rate of 7°C / min to obtain a magnetic powder core.

[0122] Example 2

[0123] This embodiment provides a method for preparing insulating coated Sendust magnetic powder, the preparation method comprising the following steps:

[0124] S1. Annealing pretreatment of 150-mesh Sendust magnetic powder at 600°C for 1 hour in a nitrogen atmosphere, with a heating rate of 5°C / min. The content of Al in the Sendust magnetic powder is 4wt%, the content of Si is 10wt%, and the balance is Fe. Then, 1kg of the annealed sendust magnetic powder is mixed with a 15wt% polyoxyethylene ether solution, wherein the polyoxyethylene ether solution is prepared from 7.5g of polyoxyethylene ether powder and 42.5g of water. After drying at 120°C for 120min, the dried product is sieved with a sieve with a mesh size of 80 to obtain the pretreated sendust magnetic powder.

[0125] S2. Mix 14 g of glucose with 186 g of water to obtain a glucose aqueous solution with a concentration of 7 wt %, take 500 g of the pretreated Sendust magnetic powder obtained in step S1 and the obtained glucose aqueous solution for hydrothermal reaction at 260°C for 30 min, and after cooling, separate the products of the hydrothermal reaction, wash the separated solid with ethanol, and then dry it at 80°C for 1.5 h, use magnetic separation to remove carbon balls not attached to the surface of the magnetic powder, and then crush the magnetically separated product to obtain a first magnetic powder, wherein the first magnetic powder includes Sendust magnetic powder and a porous carbon layer on the surface of the Sendust magnetic powder.

[0126] S3. Mix 12 g of aluminum chloride and 188 g of water to obtain an aluminum chloride solution with a concentration of 6 wt%, then add the first magnetic powder obtained in step S2, and mix them under heating conditions at 50°C for 1 hour. After separating the mixed product, the obtained solid is washed with ethanol, and then dried at 80°C for 2 hours, and then the dried product is crushed to obtain a second magnetic powder, wherein the second magnetic powder includes sendust magnetic powder, a porous carbon layer located on the surface of the sendust magnetic powder, and aluminum ions adsorbed on the surface of the porous carbon layer.

[0127] S4. In an oxygen-containing nitrogen atmosphere with an oxygen content of 5 vol%, the second magnetic powder obtained in step S3 is placed in a tubular furnace, heated to 500°C at a heating rate of 10°C / min, and heat treated for 0.5 h to obtain an insulating coated Sendust magnetic powder.

[0128] This embodiment also provides a method for preparing a magnetic powder core, the preparation method comprising the following steps:

[0129] The insulating coated Sendust magnetic powder prepared above was mixed with methyl silicone resin and zinc stearate release agent, wherein the amount of methyl silicone resin added was 0.3wt% of the mass of the insulating coated Sendust magnetic powder, and the amount of zinc stearate added was 0.1wt% of the mass of the insulating coated Sendust magnetic powder. After drying, the mixture was sieved with a sieve with a mesh number of 80 to obtain a mixed material, and the mixed material was pressed into shape under a press at 1200MPa to obtain a sample ring. The obtained sample ring was placed in a nitrogen atmosphere, heated to 600°C at 15°C / min, and kept warm for 2h. Then, the mixture was cooled to 25°C at a cooling rate of 5°C / min to obtain a magnetic powder core.

[0130] Example 3

[0131] This embodiment provides a method for preparing insulating coated Sendust magnetic powder, the preparation method comprising the following steps:

[0132] S1. annealing pretreatment of sendust magnetic powder with a particle size of 150 meshes at a temperature of 900° C. for 1 hour in a nitrogen atmosphere, the heating rate of the annealing pretreatment is 5° C. / min, the content of Al in the sendust magnetic powder is 7wt%, the content of Si is 7.5wt%, and the balance is Fe. Then, 1 kg of the annealed pretreated sendust magnetic powder is mixed with a 23wt% alkylphenol polyoxyethylene ether solution, the alkylphenol polyoxyethylene ether solution is prepared by 11.5g of alkylphenol polyoxyethylene ether and 38.5g of water, and then dried at 120° C. for 120 min, and the dried product is sieved with a sieve with a mesh number of 80 to obtain the pretreated sendust magnetic powder.

[0133] S2. Mix 40g of fructose with 160g of water to obtain a fructose aqueous solution with a concentration of 20wt%, take 500g of the pretreated Sendust magnetic powder obtained in step S1 and the obtained fructose aqueous solution for hydrothermal reaction at 225°C for 90min, and after cooling, separate the product of the hydrothermal reaction, wash the separated solid with ethanol, and then dry it at 80°C for 1.5h, remove the carbon balls not attached to the surface of the magnetic powder with magnetic separation, and then crush the magnetic separation product to obtain the first magnetic powder, wherein the first magnetic powder includes Sendust magnetic powder and a porous carbon layer on the surface of the Sendust magnetic powder.

[0134] S3. Mix 24 g of aluminum chloride and 176 g of water to obtain an aluminum chloride solution with a concentration of 12 wt%, add the first magnetic powder obtained in step S2, and mix them under heating conditions at 25°C for 6 hours. After separating the mixed product, the obtained solid is washed with ethanol, and then dried at 80°C for 2 hours. The dried product is crushed to obtain a second magnetic powder, wherein the second magnetic powder includes sendust magnetic powder, a porous carbon layer on the surface of the sendust magnetic powder, and aluminum ions adsorbed on the surface of the porous carbon layer.

[0135] S4. In an oxygen-containing nitrogen atmosphere with an oxygen content of 15 vol%, the second magnetic powder obtained in step S3 is placed in a tubular furnace, heated to 350°C at a heating rate of 2°C / min, and heat treated for 2 hours to obtain an insulating coated Sendust magnetic powder.

[0136] This embodiment also provides a method for preparing a magnetic powder core, the preparation method comprising the following steps:

[0137] The insulating coated Sendust magnetic powder prepared above was mixed with methyl silicone resin and zinc stearate release agent, wherein the amount of methyl silicone resin added was 2wt% of the mass of the insulating coated Sendust magnetic powder, and the amount of zinc stearate added was 0.6wt% of the mass of the insulating coated Sendust magnetic powder. After drying, the mixture was sieved with a sieve with a mesh number of 80 to obtain a mixed material, and the mixed material was pressed into shape under a press at 2200MPa to obtain a sample ring. The obtained sample ring was placed in a nitrogen atmosphere, heated to 800°C at 5°C / min, and the holding time was 0.5h. Then, the temperature was cooled to 25°C at a cooling rate of 10°C / min to obtain a magnetic powder core.

[0138] Example 4

[0139] The difference between this embodiment and embodiment 1 is that the aluminum chloride in step S3 is replaced with titanium chloride. The other contents are the same as those in embodiment 1.

[0140] Example 5

[0141] The difference between this embodiment and embodiment 1 is that the aluminum chloride in step S3 is replaced by a mixture of 25 wt % nickel chloride, 50 wt % ferric chloride and 25 wt % zinc sulfate. The other contents are the same as those in embodiment 1.

[0142] Example 6

[0143] This embodiment provides a method for preparing an insulating coated iron silicon magnetic powder, the preparation method comprising the following steps:

[0144] S1. The iron silicon magnetic powder with a particle size of 150 mesh is annealed at a temperature of 810°C for 1 hour in a nitrogen atmosphere, and the heating rate of the annealing pretreatment is 5°C / min. The Si content in the iron silicon powder is 4.5wt%, and the balance is Fe. Then, 1kg of the annealed iron silicon magnetic powder is mixed with a polyvinyl alcohol solution with a concentration of 20wt%, and the polyvinyl alcohol solution is prepared by 10g of polyvinyl alcohol powder and 40g of water. After drying at 120°C for 120min, the dried product is sieved with a sieve with a mesh size of 80 to obtain the pretreated iron silicon magnetic powder.

[0145] S2. Mix 20g of sucrose with 180g of water to obtain a sucrose aqueous solution with a concentration of 10wt%, take 500g of the pretreated iron silicon magnetic powder obtained in step S1 and the obtained sucrose aqueous solution to perform a hydrothermal reaction at 250°C for 60min, and after cooling, separate the products of the hydrothermal reaction, wash the separated solid with ethanol, and then dry it at 80°C for 1.5h, remove the carbon balls not attached to the surface of the magnetic powder with magnetic separation, and then crush the magnetically separated product to obtain a first magnetic powder, wherein the first magnetic powder includes iron silicon magnetic powder and a porous carbon layer on the surface of the iron silicon magnetic powder.

[0146] S3. Mix 18 g of magnesium chloride and 182 g of water to obtain a magnesium chloride solution with a concentration of 9 wt%, add the first magnetic powder obtained in step S2, and mix them under heating conditions at 40°C for 2 hours. After separating the mixed product, the obtained solid is washed with ethanol, and then dried at 80°C for 2 hours, and then the dried product is crushed to obtain a second magnetic powder, wherein the second magnetic powder includes iron silicon magnetic powder, a porous carbon layer located on the surface of the iron silicon magnetic powder, and magnesium ions adsorbed on the surface of the porous carbon layer.

[0147] S4. In an oxygen-containing nitrogen atmosphere with an oxygen content of 8 vol%, the second magnetic powder obtained in step S3 is placed in a tubular furnace, heated to 410°C at a heating rate of 5°C / min, and heat treated for 1 hour to obtain an insulating coated iron silicon magnetic powder.

[0148] This embodiment also provides a method for preparing a magnetic powder core, the preparation method comprising the following steps:

[0149] The insulating coated iron silicon magnetic powder prepared above was mixed with methyl silicone resin and zinc stearate release agent, wherein the amount of methyl silicone resin added was 0.8wt% of the mass of the insulating coated iron silicon magnetic powder, and the amount of zinc stearate added was 0.4wt% of the mass of the insulating coated iron silicon magnetic powder. After drying, the mixture was sieved with a sieve with a mesh number of 80 to obtain a mixed material, and the mixed material was pressed into shape under a press at 2000MPa to obtain a sample ring. The obtained sample ring was placed in a nitrogen atmosphere, heated to 700°C at 10°C / min, and kept warm for 1h, and then cooled to 25°C at a rate of 7°C / min to obtain a magnetic powder core.

[0150] Example 7

[0151] This embodiment provides a method for preparing an insulating coated iron silicon magnetic powder, the preparation method comprising the following steps:

[0152] S1. The iron silicon magnetic powder with a particle size of 150 mesh is annealed at a temperature of 600°C for 1 hour in a nitrogen atmosphere. The heating rate of the annealing pretreatment is 5°C / min. The Si content in the iron silicon magnetic powder is 3.5wt%, and the balance is Fe. Then, 1kg of the annealed iron silicon magnetic powder is mixed with a polyoxyethylene ether solution with a concentration of 15wt%, and the polyoxyethylene ether solution is prepared by 7.5g of polyoxyethylene ether powder and 42.5g of water. After drying at 120°C for 120min, the dried product is sieved with a sieve with a mesh size of 80 to obtain the pretreated iron silicon magnetic powder.

[0153] S2. Mix 14 g of glucose with 186 g of water to obtain a glucose aqueous solution with a concentration of 7 wt %, take 500 g of the pretreated iron silicon magnetic powder obtained in step S1 and the obtained glucose aqueous solution for hydrothermal reaction at 260°C for 30 min, and after cooling, separate the products of the hydrothermal reaction, wash the separated solid with ethanol, and then dry it at 80°C for 1.5 h, use magnetic separation to remove carbon balls not attached to the surface of the magnetic powder, crush the magnetically separated product to obtain a first magnetic powder, wherein the first magnetic powder includes iron silicon magnetic powder and a porous carbon layer on the surface of the iron silicon magnetic powder.

[0154] S3. Mix 12 g of magnesium chloride and 188 g of water to obtain a magnesium chloride solution with a concentration of 6 wt%, add the first magnetic powder obtained in step S2, and mix them under heating conditions at 50°C for 1 hour. After separating the mixed product, the obtained solid is washed with ethanol, and then dried at 80°C for 2 hours, and then the dried product is crushed to obtain a second magnetic powder, wherein the second magnetic powder includes iron silicon magnetic powder, a porous carbon layer located on the surface of the iron silicon magnetic powder, and magnesium ions adsorbed on the surface of the porous carbon layer.

[0155] S4. In an oxygen-containing nitrogen atmosphere with an oxygen content of 5 vol%, the second magnetic powder obtained in step S3 is placed in a tubular furnace, heated to 500°C at a heating rate of 10°C / min and subjected to heat treatment for 0.5 h to obtain an insulating coated iron silicon magnetic powder.

[0156] This embodiment also provides a method for preparing a magnetic powder core, the preparation method comprising the following steps:

[0157] The insulating coated iron silicon magnetic powder prepared above was mixed with methyl silicone resin and zinc stearate release agent, wherein the amount of methyl silicone resin added was 0.3wt% of the mass of the insulating coated iron silicon magnetic powder, and the amount of zinc stearate added was 0.1wt% of the mass of the insulating coated iron silicon magnetic powder. After drying, the mixture was sieved with a sieve with a mesh number of 80 to obtain a mixed material, and the mixed material was pressed into shape under a press at 1200MPa to obtain a sample ring, and the obtained sample ring was placed in a nitrogen atmosphere, heated to 600°C at 15°C / min, and kept warm for 2h, and then cooled to 25°C at a cooling rate of 5°C / min to obtain a magnetic powder core.

[0158] Example 8

[0159] This embodiment provides a method for preparing an insulating coated iron silicon magnetic powder, the preparation method comprising the following steps:

[0160] S1. annealing pretreatment of ferrosilicon magnetic powder with a particle size of 150 meshes at a temperature of 900° C. for 1 hour in a nitrogen atmosphere, the heating rate of the annealing pretreatment is 5° C. / min, the Si content in the ferrosilicon powder is 6.5wt%, and the remainder is Fe. Then, 1kg of the annealed ferrosilicon magnetic powder is mixed with an alkylphenol polyoxyethylene ether solution with a concentration of 23wt%, the alkylphenol polyoxyethylene ether solution being prepared by 11.5g of alkylphenol polyoxyethylene ether and 38.5g of water, and then dried at 120° C. for 120min, and the dried product is sieved with a sieve with a mesh number of 80 to obtain the pretreated ferrosilicon magnetic powder.

[0161] S2. Mix 40g of fructose with 160g of water to obtain a fructose aqueous solution with a concentration of 20wt%, take 500g of the pretreated iron silicon magnetic powder obtained in step S1 and the obtained fructose aqueous solution for hydrothermal reaction at 225°C for 90min, and after cooling, separate the products of the hydrothermal reaction, wash the separated solid with ethanol, and then dry it at 80°C for 1.5h, remove the carbon balls not attached to the surface of the magnetic powder with magnetic separation, crush the magnetically separated product to obtain a first magnetic powder, wherein the first magnetic powder includes iron silicon magnetic powder and a porous carbon layer on the surface of the iron silicon magnetic powder.

[0162] S3. Mix 24 g of magnesium chloride and 176 g of water to obtain a magnesium chloride solution with a concentration of 12 wt%, add the first magnetic powder obtained in step S2, and mix them under heating conditions at 25°C for 6 hours. After separating the mixed product, the obtained solid is washed with ethanol, and then dried at 80°C for 2 hours. The dried product is crushed to obtain a second magnetic powder, wherein the second magnetic powder includes iron silicon magnetic powder, a porous carbon layer located on the surface of the iron silicon magnetic powder, and magnesium ions adsorbed on the surface of the porous carbon layer.

[0163] S4. In an oxygen-containing nitrogen atmosphere with an oxygen content of 15 vol%, the second magnetic powder obtained in step S3 is placed in a tubular furnace, heated to 350°C at a heating rate of 2°C / min for 2 hours to obtain an insulating coated iron silicon magnetic powder.

[0164] This embodiment also provides a method for preparing a magnetic powder core, the preparation method comprising the following steps:

[0165] The insulating coated iron silicon magnetic powder prepared above is mixed with methyl silicone resin and zinc stearate release agent, wherein the amount of methyl silicone resin added is 2wt% of the mass of the insulating coated iron silicon magnetic powder, and the amount of zinc stearate added is 0.6wt% of the mass of the insulating coated iron silicon magnetic powder. After drying, the mixture is sieved with a sieve with a mesh number of 80 to obtain a mixed material, and the mixed material is pressed into shape under a press at 2200MPa to obtain a sample ring. The obtained sample ring is placed in a nitrogen atmosphere, heated to 800°C at 5°C / min, and the heat preservation time is 0.5h. Then, the temperature is cooled to 25°C at a cooling rate of 10°C / min to obtain a magnetic powder core.

[0166] Example 9

[0167] This embodiment provides a method for preparing an insulating coated iron-nickel magnetic powder, the preparation method comprising the following steps:

[0168] S1. The iron-nickel magnetic powder with a particle size of 150 mesh is annealed at a temperature of 810° C. for 1 hour in a nitrogen atmosphere, the heating rate of the annealing pretreatment is 5° C. / min, the Ni content in the iron-nickel magnetic powder is 45wt%, and the balance is Fe. Then, 1 kg of the annealed iron-nickel magnetic powder is mixed with a polyvinyl alcohol solution with a concentration of 20wt%, the polyvinyl alcohol solution is prepared by 10g of polyvinyl alcohol powder and 40g of water, and then dried at 120° C. for 120 minutes, and the dried product is sieved with a sieve with a mesh number of 80 to obtain the pretreated iron-nickel magnetic powder.

[0169] S2. Mix 20 g of sucrose with 180 g of water to obtain a sucrose aqueous solution with a concentration of 10 wt%, take 500 g of the pretreated iron-nickel magnetic powder obtained in step S1 and the obtained sucrose aqueous solution to perform a hydrothermal reaction at 250°C for 60 min, and after cooling, separate the product of the hydrothermal reaction, wash the separated solid with ethanol, and then dry it at 80°C for 1.5 h, remove the carbon balls not attached to the surface of the magnetic powder by magnetic separation, and then crush the magnetically separated product to obtain a first magnetic powder, wherein the first magnetic powder includes iron-nickel magnetic powder and a porous carbon layer on the surface of the iron-nickel magnetic powder.

[0170] S3. Mix 18 g of zinc sulfate and 182 g of water to obtain a zinc sulfate solution with a concentration of 9 wt%, add the first magnetic powder obtained in step S2, and mix them under heating conditions at 40°C for 2 hours. After separating the mixed product, the obtained solid is washed with ethanol, and then dried at 80°C for 2 hours, and then the dried product is crushed to obtain a second magnetic powder, wherein the second magnetic powder includes iron-nickel magnetic powder, a porous carbon layer on the surface of the iron-nickel magnetic powder, and zinc ions adsorbed on the surface of the porous carbon layer.

[0171] S4. In an oxygen-containing nitrogen atmosphere with an oxygen content of 10 vol%, the second magnetic powder obtained in step S3 is placed in a tubular furnace, heated to 400°C at a heating rate of 5°C / min and heat treated for 1 hour to obtain an insulating coated iron-nickel magnetic powder.

[0172] This embodiment also provides a method for preparing a magnetic powder core, the preparation method comprising the following steps:

[0173] The insulating coated iron-nickel magnetic powder prepared above was mixed with methyl silicone resin and zinc stearate release agent, wherein the amount of methyl silicone resin added was 0.8wt% of the mass of the insulating coated iron-nickel magnetic powder, and the amount of zinc stearate added was 0.4wt% of the mass of the insulating coated iron-nickel magnetic powder. After drying, the mixture was sieved with a sieve with a mesh number of 80 to obtain a mixed material, and the mixed material was pressed into shape under a press at 2000MPa to obtain a sample ring. The obtained sample ring was placed in a nitrogen atmosphere, heated to 700°C at 10°C / min, and kept warm for 1h, and then cooled to 25°C at a rate of 7°C / min to obtain a magnetic powder core.

[0174] Example 10

[0175] This embodiment provides a method for preparing an insulating coated iron-nickel magnetic powder, the preparation method comprising the following steps:

[0176] S1. The iron-nickel magnetic powder with a particle size of 150 mesh is annealed at 600°C for 1 hour in a nitrogen atmosphere, the heating rate of the annealing pretreatment is 5°C / min, the Ni content in the iron-nickel magnetic powder is 43wt%, and the balance is Fe. Then, 1kg of the annealed iron-nickel magnetic powder is mixed with a polyoxyethylene ether solution with a concentration of 15wt%, the polyoxyethylene ether solution is prepared by 7.5g of polyoxyethylene ether powder and 42.5g of water, and then dried at 120°C for 120min, and the dried product is sieved with a sieve with a mesh size of 80 to obtain the pretreated iron-nickel magnetic powder.

[0177] S2. Mix 14 g of glucose with 186 g of water to obtain a glucose aqueous solution with a concentration of 7 wt %, take 500 g of the pretreated iron-nickel magnetic powder obtained in step S1 and the obtained glucose aqueous solution for hydrothermal reaction at 260°C for 30 min, and after cooling, separate the product of the hydrothermal reaction, wash the separated solid with ethanol, and then dry it at 80°C for 1.5 h, use magnetic separation to remove carbon balls not attached to the surface of the magnetic powder, and then crush the magnetically separated product to obtain a first magnetic powder, wherein the first magnetic powder includes iron-nickel magnetic powder and a porous carbon layer on the surface of the iron-nickel magnetic powder.

[0178] S3. Mix 12 g of zinc sulfate and 188 g of water to obtain a zinc sulfate solution with a concentration of 6 wt%, add the first magnetic powder obtained in step S2, and mix them under heating conditions at 50°C for 1 hour. After separating the mixed product, the obtained solid is washed with ethanol, and then dried at 80°C for 2 hours, and then the dried product is crushed to obtain a second magnetic powder, wherein the second magnetic powder includes iron-nickel magnetic powder, a porous carbon layer located on the surface of the iron-nickel magnetic powder, and zinc ions adsorbed on the surface of the porous carbon layer.

[0179] S4. In an oxygen-containing nitrogen atmosphere with an oxygen content of 5 vol%, the second magnetic powder obtained in step S3 is placed in a tubular furnace, heated to 500°C at a heating rate of 10°C / min and subjected to heat treatment for 0.5 h to obtain an insulating coated iron-nickel magnetic powder.

[0180] This embodiment also provides a method for preparing a magnetic powder core, the preparation method comprising the following steps:

[0181] The insulating coated iron-nickel magnetic powder prepared above was mixed with methyl silicone resin and zinc stearate release agent, wherein the amount of methyl silicone resin added was 0.3wt% of the mass of the insulating coated iron-nickel magnetic powder, and the amount of zinc stearate added was 0.1wt% of the mass of the insulating coated iron-nickel magnetic powder. After drying, the mixture was sieved with a sieve with a mesh number of 80 to obtain a mixed material, and the mixed material was pressed into shape under a press at 1200MPa to obtain a sample ring. The obtained sample ring was placed in a nitrogen atmosphere, heated to 600°C at 15°C / min, and kept warm for 2h. Then, the mixture was cooled to 25°C at a cooling rate of 5°C / min to obtain a magnetic powder core.

[0182] Embodiment 11

[0183] This embodiment provides a method for preparing an insulating coated iron-nickel magnetic powder, the preparation method comprising the following steps:

[0184] S1. annealing pretreatment of 150-mesh iron-nickel magnetic powder at 900° C. for 1 h in a nitrogen atmosphere, wherein the heating rate of the annealing pretreatment is 5° C. / min, the Ni content in the iron-nickel magnetic powder is 50wt%, and the remainder is Fe. Then, 1 kg of the annealed iron-nickel magnetic powder is mixed with a 23wt% alkylphenol polyoxyethylene ether solution, wherein the alkylphenol polyoxyethylene ether solution is prepared from 11.5 g of alkylphenol polyoxyethylene ether and 38.5 g of water. After drying at 120° C. for 120 min, the dried product is sieved through a sieve with a mesh number of 80 to obtain the pretreated iron-nickel magnetic powder.

[0185] S2. Mix 40g of fructose with 160g of water to obtain a fructose aqueous solution with a concentration of 20wt%, take 500g of the pretreated iron-nickel magnetic powder obtained in step S1 and the obtained fructose aqueous solution for hydrothermal reaction at 225°C for 90min, and after cooling, separate the product of the hydrothermal reaction, wash the separated solid with ethanol, and then dry it at 80°C for 1.5h, remove the carbon balls not attached to the surface of the magnetic powder with magnetic separation, crush the magnetically separated product to obtain a first magnetic powder, wherein the first magnetic powder includes iron-nickel magnetic powder and a porous carbon layer located on the surface of the iron-nickel magnetic powder.

[0186] S3. Mix 24 g of zinc sulfate and 176 g of water to obtain a zinc sulfate solution with a concentration of 12 wt%, add the first magnetic powder obtained in step S2, and mix them under heating conditions at 25° C. for 6 hours. After separating the mixed product, the obtained solid is washed with ethanol, and then dried at 80° C. for 2 hours. The dried product is crushed to obtain a second magnetic powder, wherein the second magnetic powder includes iron-nickel magnetic powder, a porous carbon layer on the surface of the iron-nickel magnetic powder, and zinc ions adsorbed on the surface of the porous carbon layer.

[0187] S4. In an oxygen-containing nitrogen atmosphere with an oxygen content of 15 vol%, the second magnetic powder obtained in step S3 is placed in a tubular furnace, heated to 350°C at a heating rate of 2°C / min for 2 hours to obtain an insulating coated iron-nickel magnetic powder.

[0188] This embodiment also provides a method for preparing a magnetic powder core, the preparation method comprising the following steps:

[0189] The insulating coated iron-nickel magnetic powder prepared above is mixed with methyl silicone resin and zinc stearate release agent, wherein the amount of methyl silicone resin added is 2wt% of the mass of the insulating coated iron-nickel magnetic powder, and the amount of zinc stearate added is 0.6wt% of the mass of the insulating coated iron-nickel magnetic powder. After drying, the mixture is sieved with a sieve with a mesh number of 80 to obtain a mixed material, and the mixed material is pressed into shape under a press at 2200MPa to obtain a sample ring. The obtained sample ring is placed in a nitrogen atmosphere, heated to 800°C at 5°C / min, and the holding time is 0.5h. Then, the temperature is cooled to 25°C at a cooling rate of 10°C / min to obtain a magnetic powder core.

[0190] Example 12

[0191] The difference between this embodiment and embodiment 1 is that in the method for preparing the insulating coated sendust magnetic powder provided in this embodiment, the carbon source fructose in step S2 is replaced by graphite. The rest of the contents are the same as those in embodiment 1.

[0192] Example 13

[0193] The difference between this embodiment and embodiment 1 is that in the method for preparing the insulating coated sendust magnetic powder provided in this embodiment, the concentration of the carbon source in step S2 is 1 wt %. The rest of the contents are the same as those in embodiment 1.

[0194] Embodiment 14

[0195] The difference between this embodiment and embodiment 1 is that in the method for preparing the insulating coated sendust magnetic powder provided in this embodiment, the concentration of the carbon source in step S2 is 30 wt %. The rest of the contents are the same as those in embodiment 1.

[0196] Embodiment 15

[0197] The difference between this embodiment and embodiment 1 is that in the method for preparing the insulating coated sendust magnetic powder provided in this embodiment, the temperature of the hydrothermal reaction in step S2 is 100° C. The rest of the contents are the same as those in embodiment 1.

[0198] Example 16

[0199] The difference between this embodiment and embodiment 1 is that in the method for preparing the insulating coated sendust magnetic powder provided in this embodiment, the temperature of the hydrothermal reaction in step S2 is 300° C. The rest of the contents are the same as those in embodiment 1.

[0200] Embodiment 17

[0201] The difference between this embodiment and embodiment 1 is that in the method for preparing insulating coated sendust magnetic powder provided in this embodiment, the concentration of the aluminum chloride solution in step S3 is 1 wt %. The rest of the contents are the same as those in embodiment 1.

[0202] Embodiment 18

[0203] The difference between this embodiment and embodiment 1 is that in the method for preparing the insulating coated sendust magnetic powder provided in this embodiment, the concentration of the aluminum chloride solution in step S3 is 20 wt %. The rest of the contents are the same as those in embodiment 1.

[0204] Embodiment 19

[0205] The difference between this embodiment and embodiment 1 is that in the method for preparing the insulating coated sendust magnetic powder provided in this embodiment, the time for mixing the first magnetic powder with the aluminum chloride solution in step S3 is 30 minutes. The rest of the contents are the same as those in embodiment 1.

[0206] Embodiment 20

[0207] The difference between this embodiment and embodiment 1 is that in the method for preparing the insulating coated sendust magnetic powder provided in this embodiment, the time for mixing the first magnetic powder with the aluminum chloride solution in step S3 is 8 hours. The rest of the contents are the same as those in embodiment 1.

[0208] Embodiment 21

[0209] The difference between this embodiment and embodiment 1 is that in the method for preparing the insulating coated sendust magnetic powder provided in this embodiment, the temperature of the heat treatment in step S4 is 200° C. The rest of the contents are the same as those in embodiment 1.

[0210] Embodiment 22

[0211] The difference between this embodiment and embodiment 1 is that in the method for preparing the insulating coated sendust magnetic powder provided in this embodiment, the temperature of the heat treatment in step S4 is 600° C. The rest of the contents are the same as those in embodiment 1.

[0212] Embodiment 23

[0213] The difference between this embodiment and embodiment 1 is that in the method for preparing the insulating coated sendust magnetic powder provided in this embodiment, the heat treatment time in step S4 is 10 minutes. The rest of the contents are the same as those in embodiment 1.

[0214] Embodiment 24

[0215] The difference between this embodiment and embodiment 1 is that in the method for preparing the insulating coated sendust magnetic powder provided in this embodiment, the heat treatment time in step S4 is 3 hours. The rest of the contents are the same as those in embodiment 1.

[0216] Embodiment 25

[0217] The difference between this embodiment and embodiment 1 is that in the method for preparing insulating coated sendust magnetic powder provided in this embodiment, the oxygen content of the oxygen-containing nitrogen atmosphere in the heat treatment in step S4 is 1 vol%. The rest of the contents are the same as those in embodiment 1.

[0218] Embodiment 26

[0219] The difference between this embodiment and embodiment 1 is that in the method for preparing the insulating coated sendust magnetic powder provided in this embodiment, the heat treatment gas in step S4 is replaced by air. The rest of the contents are the same as those in embodiment 1.

[0220] Embodiment 27

[0221] The difference between this embodiment and embodiment 1 is that in the method for preparing the insulating coated sendust magnetic powder provided in this embodiment, the surface pretreatment process in step S1 is omitted. The rest of the contents are the same as those in embodiment 1.

[0222] Comparative Example 1

[0223] The difference between this comparative example and Example 1 is that in the preparation method of the insulating coated sendust magnetic powder provided in this comparative example, step S2 to step S4 are omitted, and the nano-alumina insulating agent with a mass percentage of 2wt% is directly mixed with the pretreated sendust magnetic powder. The rest of the contents are the same as Example 1.

[0224] Comparative Example 2

[0225] The difference between this comparative example and Example 6 is that in the preparation method of the insulating coated iron silicon magnetic powder provided in this comparative example, step S2 to step S4 are omitted, and the nano magnesium oxide insulating agent with a mass percentage of 2wt% is directly mixed with the pretreated iron silicon magnetic powder. The rest of the contents are the same as Example 6.

[0226] Comparative Example 3

[0227] The difference between this comparative example and Example 9 is that in the preparation method of the insulating coated iron-nickel magnetic powder provided in this comparative example, step S2 to step S4 are omitted, and the nano zinc oxide insulating agent with a mass percentage of 2wt% is directly mixed with the pretreated iron-nickel magnetic powder. The rest of the contents are the same as Example 9.

[0228] The magnetic powder cores obtained in Examples 1-27 and Comparative Examples 1-3 were tested for inductance, DC superposition, magnetic loss and resistivity. The test results are shown in Table 1.

[0229] Among them: (1) Inductance test: test instrument: CH3302 inductance tester, test frequency and voltage: 100kHz / 1V, test turns: 0.4mm, 25Ts;

[0230] (2) DC superposition test: Test instrument: CH3302 inductance tester, test frequency and voltage: 100kHz / 1V, test turns: 0.4mm, 25Ts, test current: 0A, 20A;

[0231] (3) Magnetic loss test: Test instrument: SY8218 power consumption tester, test conditions: 50kHz / 100mT, test turns: 0.4mm, 22×22Ts;

[0232] (4) Resistivity test: The four-probe method was used to test the resistivity of the magnetic powder cores prepared by the preparation methods provided in the above Examples 1-27 and Comparative Examples 1-3. The test structure is shown in Table 1.

[0233] Table 1

[0234] Inductance(μH) DC superposition (100Oe) <![CDATA[Magnetic loss (mW / cm 3 )]]> Resistivity (Ω·m) Example 1 47.1 29.8 / 63.3% 176 302 Example 2 48.3 30.1 / 62.3% 188 311 Example 3 46.5 30.3 / 65.1% 180 296 Example 4 47.9 30.7 / 64.1% 169 305 Example 5 48.2 30.8 / 63.9% 171 321 Example 6 49.6 39.6 / 79.8% 582 183 Example 7 46.1 39 / 84.6% 571 192 Example 8 47.6 39 / 81.9% 590 189 Example 9 47.2 40.2 / 85.1% 189 256 Example 10 50.1 40.7 / 81.2% 191 266 Embodiment 11 46.3 40.1 / 86.6% 182 259 Example 12 65.2 25.1 / 38.5% 220 210 Embodiment 13 53.1 25.8 / 48.6% 243 201 Embodiment 14 42.3 26.1 / 61.7% 235 233 Embodiment 15 56.2 22.3 / 39.7% 267 160 Example 16 43.9 24.6 / 56.1% 242 198 Embodiment 17 52.3 26.8 / 51.2% 202 242 Embodiment 18 40.1 24.3 / 60.6% 183 326 Embodiment 19 53.2 27.1 / 50.9% 212 248 Embodiment 20 40.2 23.9 / 59.5% 180 329 Embodiment 21 41.6 24.1 / 57.9% 246 163 Embodiment 22 42.3 24.9 / 58.9% 192 311 Embodiment 23 41.9 24.1 / 57.5% 249 166 Embodiment 24 42.1 24.5 / 58.2% 182 321 Embodiment 25 43.1 24.9 / 57.8% 245 176 Embodiment 26 40.9 23.3 / 57% 186 331 Embodiment 27 51.9 26.5 / 51.06% 201 261 Comparative Example 1 46.9 26.7 / 56.9% 203 257 Comparative Example 2 48.9 36.2 / 74.1% 602 163 Comparative Example 3 47.5 38.8 / 81.4% 212 202

[0235] The test results show that:

[0236] (1) It can be seen from Examples 1 to 2-11 that the present invention first mixes the magnetic powder and the carbon source in a solvent and then undergoes a hydrothermal reaction to form a porous carbon layer on the surface of the magnetic powder. The mixture is then mixed with a metal salt in a solvent to react, and the porous carbon layer on the surface of the magnetic powder adsorbs metal ions in the metal salt. Subsequently, an insulating oxide layer with high density, good uniformity and integrity, and high bonding strength is formed on the surface of the magnetic powder through a heat treatment process under an oxygen partial pressure. This allows the prepared insulating coated magnetic powder to form a magnetic powder core with the advantage of excellent comprehensive performance.

[0237] (2) By comparing Example 1 and Example 12, it can be seen that compared with graphite as a carbon source, the carbon source containing specific hydroxyl and / or carboxyl groups provided by the present invention can achieve the adsorption of metal ions, thereby obtaining a magnetic powder with a high density of surface-coated metal oxides, good coating uniformity and integrity, and high bonding strength.

[0238] (3) By comparing Example 1 with Examples 13-16, it can be seen that in the preparation method provided by the present invention, the concentration of the carbon source solution and the temperature of the hydrothermal reaction between the carbon source solution and the magnetic powder will affect the performance of the magnetic powder core. When the concentration of the carbon source solution or the temperature of the hydrothermal reaction is too low, a carbon layer with a better coating effect cannot be formed on the surface of the magnetic powder, and the subsequent metal ions cannot be effectively adsorbed. The prepared magnetic powder core has low resistivity, high power consumption, and poor DC superposition. When the concentration of the carbon source solution or the temperature of the hydrothermal reaction is too high, the carbon layer formed on the surface of the magnetic powder is too thick. During the subsequent heat treatment in an oxygen-containing atmosphere, on the one hand, the carbon layer cannot be completely removed, resulting in a decrease in resistivity. On the other hand, the formed oxide layer is too thick, resulting in low inductance, poor DC superposition, low resistivity and high magnetic loss of the magnetic powder core.

[0239] (4) By comparing Example 1 with Examples 17-20, it can be seen that the concentration of the metal salt solution in the preparation method provided by the present invention and the mixing time of the first magnetic powder and the metal salt solution will affect the performance of the magnetic powder core. When the concentration of the metal salt solution or the mixing time is too low, the carbon layer on the surface of the magnetic powder adsorbs too few metal ions, resulting in the inability to form a dense and complete oxide film on the surface of the magnetic powder after sintering, and the prepared magnetic powder core has low resistivity, high power consumption, and poor DC superposition; when the concentration of the metal salt solution or the mixing time is too high, the carbon layer on the surface of the magnetic powder adsorbs too many metal ions, and the oxide layer formed after sintering is too thick, resulting in low inductance and poor DC superposition of the magnetic powder core.

[0240] (5) By comparing Example 1 with Examples 21-26, it can be seen that in the preparation method provided by the present invention, the temperature, time and oxygen content of the heat treatment of the second magnetic powder will affect the performance of the magnetic powder core. When the heat treatment temperature is too low or the time is too short or the oxygen content is too low, the carbon layer on the surface of the magnetic powder cannot be completely removed, the integrity and density of the formed oxide film are reduced, and the resistivity of the prepared magnetic powder core is low, the power consumption is high, the DC superposition is poor, and the inductance characteristics are also reduced; when the heat treatment temperature is too high or the time is too long or the oxygen content is too high, on the one hand, the formed oxide grains grow and the density of the oxide layer is reduced, and on the other hand, the magnetic powder will be oxidized, the magnetic dilution is further increased, and the prepared magnetic powder core has low inductance, poor DC superposition characteristics and high magnetic loss.

[0241] (6) By comparing Example 1 with Example 27, it can be seen that the preparation method provided by the present invention omits the surface pretreatment process in step S1, and the agglomeration of the magnetic powder is not effectively improved, resulting in a decrease in the density and integrity of the carbon layer formed in the subsequent process, thereby causing the inductance of the prepared Sendust magnetic powder core to exceed a reasonable range, the 100Oe DC superposition characteristics are also significantly reduced, and the power consumption is significantly increased.

[0242] (7) By comparing Example 1 with Comparative Examples 1-3, it can be seen that compared with the preparation method of the present invention, the magnetic powder core prepared by the method of directly adding oxides has low resistivity, poor DC superposition and high power consumption. This is because the direct addition of oxides cannot form a uniform, complete and dense oxide layer on the surface of the magnetic powder.

[0243] In summary, the present invention mixes magnetic powder and a carbon source in a solvent, generates a porous carbon layer on the surface of the magnetic powder through a hydrothermal reaction, and then mixes the first magnetic powder containing the porous carbon layer with a metal salt in a solvent, and utilizes the adsorption effect of hydroxyl and carboxyl groups on the surface of the porous carbon layer on metal ions to make the porous carbon layer on the surface of the magnetic powder rich in metal ions, and then places the obtained second magnetic powder in an oxygen-containing atmosphere for a heat treatment process to control the decomposition of the porous carbon layer and the formation of metal oxides, thereby obtaining a magnetic powder with a high density of surface-coated metal oxides, good coating uniformity and integrity, and high bonding strength, which can promote the magnetic powder core composed of the insulating coated magnetic powder to have the advantages of high resistivity, high DC superposition characteristics and low power loss.

[0244] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing an insulating coated magnetic powder, characterized in that: The preparation method comprises the following steps: (1) mixing a magnetic powder, a carbon source and a first solvent, and subjecting the mixture to a hydrothermal reaction to obtain a first magnetic powder, wherein the first magnetic powder includes the magnetic powder and a porous carbon layer on a surface of the magnetic powder; (2) mixing the first magnetic powder, the metal salt and the second solvent to obtain a second magnetic powder, wherein the second magnetic powder includes the magnetic powder, a porous carbon layer located on the surface of the magnetic powder, and metal ions adsorbed on the surface of the porous carbon layer; (3) Heat treating the second magnetic powder in an oxygen-containing atmosphere to obtain the insulating coated magnetic powder.

2. The preparation method according to claim 1, characterized in that: The magnetic powder in step (1) includes any one of iron silicon magnetic powder, sendust magnetic powder or iron nickel magnetic powder; Preferably, the particle size of the magnetic powder in step (1) is less than 150 mesh; Preferably, in step (1), the magnetic powder is pretreated before the mixing is performed; Preferably, the pretreatment includes annealing pretreatment; Preferably, the pretreatment further comprises: performing annealing pretreatment on the magnetic powder and then performing surface pretreatment; Preferably, the temperature of the annealing pretreatment is 600-900°C; Preferably, the heating rate of the annealing pretreatment is 3-10°C / min; Preferably, the annealing pretreatment time is 0.5-2h; Preferably, the atmosphere of the annealing pretreatment includes any one of a hydrogen atmosphere, a nitrogen atmosphere or an argon atmosphere, or a combination of at least two thereof; Preferably, the specific process of the surface pretreatment includes: mixing the surface treatment agent with the annealed pretreated magnetic powder, and then drying to obtain the pretreated magnetic powder for mixing with the carbon source; Preferably, the surface treatment agent includes any one of polyvinyl alcohol, polyoxyethylene ether or alkylphenol polyoxyethylene ether; Preferably, the concentration of the surface treatment agent is 15-23wt%; Preferably, during the surface pretreatment process, the mass ratio of the surface treatment agent to the magnetic powder is (0.04-0.07):1; Preferably, during the surface pretreatment process, the drying temperature is 60-150°C; Preferably, during the surface pretreatment process, the drying time is 30-120 minutes.

3. The preparation method according to claim 1 or 2, characterized in that: The carbon source in step (1) includes a carbon source containing hydroxyl groups and / or carboxyl groups; Preferably, the carbon source in step (1) comprises any one of glucose, fructose, sucrose, maltose, starch and citric acid, or a combination of at least two thereof; Preferably, in step (1), the first solvent comprises water; Preferably, the specific process of the mixing in step (1) includes: mixing the carbon source with the first solvent to obtain a carbon source solution, and then mixing the carbon source solution with the magnetic powder to obtain a mixed solution for hydrothermal reaction; Preferably, the concentration of the carbon source in the carbon source solution is 7-20wt%; Preferably, the mass ratio of the magnetic powder to the carbon source solution is (2-4):1; Preferably, the temperature of the hydrothermal reaction in step (1) is 225-260°C; Preferably, the hydrothermal reaction time in step (1) is 30-90 min; Preferably, after the hydrothermal reaction in step (1), the product of the hydrothermal reaction is subjected to a first separation, a first washing, a first drying and a magnetic separation in sequence; Preferably, the first drying temperature is 70-100°C; Preferably, the first drying time is 1-2 hours.

4. The preparation method according to any one of claims 1 to 3, characterized in that The metal salt in step (2) includes any one of iron salt, aluminum salt, titanium salt, zinc salt, magnesium salt, nickel salt or manganese salt, or a combination of at least two thereof; Preferably, the second solvent in step (2) comprises any one of water, ethanol, acetone or toluene, or a combination of at least two thereof; Preferably, the specific process of the mixing in step (2) includes: mixing a metal salt with a solvent to obtain a metal salt solution, and then mixing the obtained metal salt solution with the first magnetic powder to obtain a second magnetic powder; Preferably, the concentration of the metal salt solution is 6-12wt%; Preferably, the ratio of the amount of the metal salt solution added to the amount of the magnetic powder added in step (1) is 1:(2-4); Preferably, the mixing in step (2) is also accompanied by heating; Preferably, the mixing temperature in step (2) is 25-50°C; Preferably, the mixing time in step (2) is 1-6 hours; Preferably, after the mixing in step (2), the mixed product is subjected to a second separation, a second washing and a second drying in sequence; Preferably, the second drying temperature is 70-100°C; Preferably, the second drying time is 1-2 hours.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The temperature of the heat treatment in step (3) is 350-500°C; Preferably, the heating rate of the heat treatment in step (3) is 2-10°C / min; Preferably, the heat treatment time in step (3) is 0.5-2h; Preferably, the oxygen-containing atmosphere in step (3) comprises oxygen; Preferably, the oxygen-containing atmosphere in step (3) further comprises nitrogen and / or an inert gas; Preferably, the oxygen content in the oxygen-containing atmosphere in step (3) is 5-15 vol%.

6. An insulating coated magnetic powder, characterized in that: The insulating coated magnetic powder is prepared by the preparation method according to any one of claims 1 to 5.

7. The insulating coated magnetic powder according to claim 6, characterized in that: The insulating coated magnetic powder comprises magnetic powder and a metal oxide coated on the surface of the magnetic powder.

8. A magnetic powder core, characterized in that: The magnetic powder core comprises the insulation-coated magnetic powder according to claim 6 or 7.

9. A method for preparing a magnetic powder core according to claim 8, characterized in that: The preparation method comprises: The insulating coated magnetic powder according to claim 6 or 7, a binder and a release agent are mixed, and then pressed and sintered to obtain the magnetic powder core.

10. The method for preparing a magnetic powder core according to claim 9, characterized in that: The binder includes any one of silicone resin, epoxy resin, phenolic resin or acrylic resin, or a combination of at least two of them; Preferably, the amount of the binder added is 0.3-2wt% of the mass of the insulation-coated magnetic powder; Preferably, the release agent comprises any one of zinc stearate, aluminum stearate or talc, or a combination of at least two thereof; Preferably, the amount of the release agent added is 0.1-0.6wt% of the mass of the insulation-coated magnetic powder; Preferably, after the mixing, the mixed product is screened; Preferably, the mesh size of the sieve is 60-100 meshes; Preferably, the pressure of the compression molding is 1200-2200 MPa; Preferably, the sintering temperature is 600-800°C; Preferably, the heating rate of the sintering is 5-15°C / min; Preferably, the sintering time is 0.5-2h; Preferably, the sintering temperature reduction rate is 5-10°C / min; Preferably, the gas used in the sintering atmosphere includes any one of hydrogen, nitrogen or argon, or a combination of at least two of them.

Citation Information

Patent Citations

  • Inorganic insulating adhesive for soft magentic metal powder core andits prepn process

    CN101089108A

  • Preparation method of metal soft magnetic powder core

    CN103247403A